Effect of Orthodontic Tooth Movement on Salivary Aspartate Aminotransferase Activity - Steiven Adhitya; Janti Sudiono; Joko Kusnoto; Boedi O. Roeslan (Faculty of Dentistry, Universitas Indonesia, 2013)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">Aspartate aminotransferase is one of biological indicator in gingival crevicular fluid (CGF). Force orthodontic application could increase activity of aspartate aminotransferase in CGF. However, the increase activity of aspartate aminotransferase in saliva due to orthodontic force and its correlation between aspartate aminotransferase activity and tooth movement remains unclear. Objectives: To evaluate application orthodontic force on the aspartate aminotransferase activity in saliva based on the duration of force and finding correlation between tooth movement and aspartate aminotransferase activity. Methods: Twenty saliva samples collected before extraction of first premolar, at the time of force application for canine retraction and after force application. The canines retraction used 100 grams of interrupted force (module chain) for thirty days. The collection of saliva and the measurement of tooth movement were carried out 1 day, 7 days, 14 days, 21 days, and 28 days after force application. The measurement of aspartate aminotransferase activity in saliva was done using spectrophotometer. Results: Application of orthodontic force influences the salivary aspartate aminotransferase activity (F=25.290, p=0.000). Furthermore, tooth movement correlated with aspartate aminotransferase activity (F=0.429, p=0.000). Conclusion: Aspartate aminotransferase activity could be used as tooth movement indicator that related to the duration of force application. <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">DOI : 10.14693/jdi.v20i1.128